Analisis Pengaruh Upah Dan Insentif Terhadap Produktivitas Kerja Karyawan PT Artamas Kurnia Bekasi: Analysis of the Impact of Wages and Incentives on Employee Productivity at PT Artamas Kurnia Bekasi - Hendy Hendy; Mahmud Syarif (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
- Technological developments cause competition. An organization is expected to have high productivity with good and quality (HR) in carrying out all its operations as a workforce. The wage level which is still very low will affect employee efforts to increase their productivity, but it is difficult to guarantee a wage increase if productivity is very low, so the author is interested in raising the problem with the title "Analysis of the Influence of Wages and Incentives on Employee Work Productivity of PT. Artamas Kurnia Bekasi" in this study was conducted with a quantitative approach and the method used was the distribution of questionnaires and what was obtained was 46 employees. The value of this r table was obtained from a significant value of 5% with a total data of 46 respondents with a result of 0.290 if r count r table then the statement is declared valid. The wage system variable is known to be t count 4.537 t table 2.011 and a significant value of 0.05 then H1 is accepted. and It is known that sig for the influence of X2 on Y is 0.05 then H2 is accepted. H3 There is an assumption that the variables of Wage Influence (X1) and Incentives (X2) have a significant influence on Work Productivity (Y). Based on this research and the discussion carried out, the analysis of the influence of wages and incentives on employee work productivity at PT Artmas Kurnia Bekasi. The conclusion of this scientific work Wages and Incentives have an important influence on the Work Productivity of Employees of PT. Artamas Kurnia Bekasi. And significant